2017
DOI: 10.1139/cjpp-2017-0265
|View full text |Cite
|
Sign up to set email alerts
|

Na+–H+exchanger and proton channel in heart failure associated with Becker and Duchenne muscular dystrophies

Abstract: Cardiomyopathy is found in patients with Duchenne (DMD) and Becker (BMD) muscular dystrophies, which are linked muscle diseases caused by mutations in the dystrophin gene. Dystrophin defects are not limited to DMD but are also present in mild BMD. The hereditary cardiomyopathic hamster of the UM-X7.1 strain is a particular experimental model of heart failure (HF) leading to early death in muscular dystrophy (dystrophin deficiency and sarcoglycan mutation) and heart disease (␦-sarcoglycan deficiency and dystrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…Intracellular calcium overload in DMD cardiomyocytes can also arise form an altered function of other channels, such as Na + -H + exchanger (NHE-1) and proton channels [66]. An increased Na + influx through NHE-1 leads to an intracellular accumulation that, in turn, promotes calcium influx through the Na + -Ca +2 exchanger.…”
Section: Calcium Handlingmentioning
confidence: 99%
“…Intracellular calcium overload in DMD cardiomyocytes can also arise form an altered function of other channels, such as Na + -H + exchanger (NHE-1) and proton channels [66]. An increased Na + influx through NHE-1 leads to an intracellular accumulation that, in turn, promotes calcium influx through the Na + -Ca +2 exchanger.…”
Section: Calcium Handlingmentioning
confidence: 99%
“…A recently completed study in Golden Retriever muscular dystrophy (GRMD) dogs has confirmed the cardioprotective role of Rimeporide after a treatment in a preventing setting [ 12 ]. Other preclinical experiments [ 13 , 14 ] have underlined the significance of myocardial necrosis, due to pH abnormalities as well as calcium and sodium imbalances in the pathophysiology of heart failure and have demonstrated the beneficial effects of NHE-1 inhibition using Rimeporide in preventing the deleterious effects of Ca2+ and Na + overload [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hereditary cardiomyopathic hamster is one of the best models for hypertrophy and heart failure associated with increased ROS levels (Dhalla et al, 1996;Wu et al, 2012;Mollnau et al, 2005;Escobales and Crespo, 2006). Hence, in this study, using the wellknown animal model of hypertrophy and heart failure, the UM-X7.1 hereditary cardiomyopathic hamster (Jacques and Bkaily, 2018;Bkaily and Jacques, 2017;Bkaily et al, 2015), we verified whether the density of certain types of NOXs particularly NOXs 1 and 3 undergo changes during the development of heart failure.…”
Section: R a F Tmentioning
confidence: 55%